Human Cumulus Cells in Long-Term In Vitro Culture Reflect Differential Expression Profile of Genes Responsible for Planned Cell Death and Aging-A Study of New Molecular Markers - Chermuła, Błażej; Kranc, Wiesława; Jopek, Karol; Budna-Tukan, Joanna; Hutchings, Greg; Dompe, Claudia; Moncrieff, Lisa; Janowicz, Krzysztof; Józkowiak, Małgorzata; Jeseta, Michal; Petitte, Jim; Mozdziak, Paul; et al. (Cells, 2020)
In the ovarian follicle, maturation of the oocyte increases in the presence of somatic cells called cumulus cells (CCs). These cells form a direct barrier between the oocyte and external environment. Thanks to bidirectional communication, they have a direct impact on the oocyte, its quality and development potential. Understanding the genetic profile of CCs appears to be important in elucidating the physiology of oocytes. Long-term in vitro culture of CCs collected from patients undergoing controlled ovarian stimulation during in vitro fertilization procedure was conducted. Using microarray expression analysis, transcript levels were assessed on day 1, 7, 15, and 30 of culture. Apoptosis and aging of CCs strictly influence oocyte quality and subsequently the outcome of assisted reproductive technologies (ART). Thus, particular attention was paid to the analysis of genes involved in programmed cell death, aging, and apoptosis. Due to the detailed level of expression analysis of each of the 133 analyzed genes, three groups were selected: first with significantly decreased expression during the culture; second with the statistically lowest increase in expression; and third with the highest significant increase in expression. COL3A1, SFRP4, CTGF, HTR2B, VCAM1, TNFRSF11B genes, belonging to the third group, were identified as potential carriers of information on oocyte quality.
Keywords: buněčná smrt; Reproducibility of Results; Gene Expression Profiling; analýza hlavních komponent; reprodukovatelnost výsledků; Cell Culture Techniques; Time Factors; Gene Ontology; Gene Expression Regulation; tvar buňky; Cellular Senescence; Adult; human; genové regulační sítě; Gene Regulatory Networks; regulace genové exprese; Cell Death; Principal Component Analysis; Cell Shape; programmed cell death; Cumulus Cells; Humans; gene expression; cumulus cells; biologické markery; časové faktory; kumulární buňky; buněčné kultury; stanovení celkové genové exprese; dospělí; Biomarkers; genová ontologie; lidé; stárnutí buněk